The Gut-Muscle Axis in Older Subjects with Low Muscle Mass and Performance: A Proof of Concept Study Exploring Fecal Microbiota Composition and Function with Shotgun Metagenomics Sequencing - Ticinesi, Andrea; Mancabelli, Leonardo; Tagliaferri, Sara; Nouvenne, Antonio; Milani, Christian; Del Rio, Daniele; Lauretani, Fulvio; Maggio, Marcello Giuseppe; Ventura, Marco; Meschi, Tiziana (International journal of molecular sciences, 2020)
The gut microbiota could influence the pathophysiology of age-related sarcopenia through multiple mechanisms implying modulation of chronic inflammation and anabolic resistance. The aim of this study was to compare the fecal microbiota composition and functionality, assessed by shotgun metagenomics sequencing, between two groups of elderly outpatients, differing only for the presence of primary sarcopenia. Five sarcopenic elderly subjects and twelve non-sarcopenic controls, classified according to lower limb function and bioimpedance-derived skeletal muscle index, provided a stool sample, which was analyzed with shotgun metagenomics approaches, to determine the overall microbiota composition, the representation of bacteria at the species level, and the prediction of bacterial genes involved in functional metabolic pathways. Sarcopenic subjects displayed different fecal microbiota compositions at the species level, with significant depletion of two species known for their metabolic capacity of producing short-chain fatty acids (SCFAs), Faecalibacterium prausnitzii and Roseburia inulinivorans, and of Alistipes shahii. Additionally, their fecal metagenome had different representation of genes belonging to 108 metabolic pathways, namely, depletion of genes involved in SCFA synthesis, carotenoid and isoflavone biotransformation, and amino acid interconversion. These results support the hypothesis of an association between microbiota and sarcopenia, indicating novel possible mediators, whose clinical relevance should be investigated in future studies.